Aerodynamic and Aeroacoustic Optimization of Propeller Based on Hanson Noise Model (Xibei Gongye Daxue Xuebao, 2020)
Aiming at the multi-objective optimization design problem of propeller aerodynamics and noise, the three-dimensional geometric deformation of the whole blade is carried out by the free-form surface deformation method based on non-uniform rational B-spline. In order to save the calculation cost of optimization, the RANS method and the Hanson model are combined to predict pure tone noise, and the prediction accuracy is comparable to the accuracy of the FW-H equation coupled with URANS method. Kriging surrogate model and non-dominated sorting genetic algorithm are used to search for optimal value, and a multi-objective optimization design framework for propeller aerodynamics and noise is established. This method is used to optimize the blade shape of a passenger airliner propeller, and the airfoil torsion angle and chord length of different positions are optimized as design variables. Compared with the basic blade, the noise value of the axial monitoring point near the cruise configuration under the wind tunnel experiment condition is reduced by about 0.25 dB at the same time as the power is reduced. In the case of a slight increase in power, the noise is reduced by about 1 dB.